The Optical Characteristics of Aggregates Organic Matter Fractions in Typical Chernozems - V. A. Kholodov; V. A. Ivanov; Ju. R. Farkhodov; N. A. Safronova; Z. S. Artemyeva; N. V. Jaroslavceva (Бюллетень Почвенного института им. В.В. Докучаева)
The consumption specters of organic matter fractions in ultraviolet and visible parts of specter (UV-visible specters) were investigated. The specters of soluted organic matter, as well as labile humic matters and humic matters itselves, which were extracted from small, medium and large aggregates from typical chernozems of long-term experiments were investigated. The samples of undisturbed chernozems, which are annually collected in the annually hayed steppe and from the chernozem with extreme organic matter degradation, were used (variant of long-termed experiment - irreplaceable black fallow since 1964). On the basis of specters obtained the parameters of optical indices SUVA254, E2/E3, E4/E6 were calculated. The highest differences between the aggregates were revealed in extracts of organic matter. The differences were lower for labile humic matters. There were no differences revealed for humic matters between the optical indices for different aggregates of one type of chernozems use. It is shown that all of the three parameters are not changed symbasically. Hence, all of the three parameters should be used for complete spectral characteristic.